THE EFFECT OF SILVICULTURAL TREATMENT ON STAND GROWTH OF LOGGED-OVER FOREST IN SOUTH PAPUA - Relawan Kuswandi (Indonesian Journal of Forestry Research, 2014)
Forest stand structure could be used as one of  the variables in deciding the possibility to harvest forest product. On logged-over forests, data and information over stand structure could become the basis for decision making for harvesting. To measure and analyze yield on logged-over forest, each forest management unit (IUPHHK) is obligated to establish Permanent Sample Plots (PSPs) for monitoring the growth and yield of  the managed stand. In some of  the plots, maintenances and thinning treatments are applied while other plots are not treated.  The results, after several years of  observations, showed that there was a difference in stand structure (tree number) of  each diameter class both in plots with treatment and without treatment. The rate of  in-growth, up-growth and mortality varied between plots without and with treatment in each diameter class and length of  time after harvesting. The average diameter increment of  trees in the stands of  the untreated plots was higher (0.60 cm yr-1) compared to the treated plots (0.55 cm yr-1).